Clostridium difficile secreted Pro‐Pro endopeptidase PPEP‐1 (ZMP1/CD2830) modulates adhesion through cleavage of the collagen binding protein CD2831. Issue 24 (29th October 2015) - Hensbergen, Paul J.; Klychnikov, Oleg I.; Bakker, Dennis; Dragan, Irina; Kelly, Michelle L.; Minton, Nigel P.; Corver, Jeroen; Kuijper, Ed J.; Drijfhout, Jan Wouter; van Leeuwen, Hans C.
Abstract : The Clostridium difficile cd2830 gene product is a secreted metalloprotease, named Pro‐Pro endopeptidase (PPEP‐1). PPEP‐1 cleaves C. difficile cell surface proteins (e.g. CD2831). Here, we confirmed that PPEP‐1 has a unique preference for prolines surrounding the scissile bond. Moreover, we show that it exhibits a high preference for an asparagine at the P2 position and hydrophobic residues at the P3 position. Using a PPEP‐1 knockout C. difficile strain, we demonstrate that the removal of the collagen binding protein CD2831 is fully attributable to PPEP‐1 activity. The PPEP‐1 knockout strain demonstrated higher affinity for collagen type I with attenuated virulence in hamsters. Abstract : C. difficile Pro‐Pro endopeptidase (PPEP‐1) has a strict preference for cleaving between two prolines. PPEP‐1 has a preference for an Asn at the P2, and a Val, Ile or Leu at the P3 position. PPEP‐1 knockout cells retain the collagen binding protein CD2831 on the cell surface. PPEP‐1 knockout cells show higher affinity for collagen type I. PPEP‐1 knockout cells show attenuated virulence in a hamster infection model.